2020
DOI: 10.1038/s41598-020-58776-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals in treated wastewater induce a stress response in tomato plants

Abstract: Pharmaceuticals remain in treated wastewater used to irrigate agricultural crops. Their effect on terrestrial plants is practically unknown. Here we tested whether these compounds can be considered as plant stress inducers. Several features characterize the general stress response in plants: production of reactive oxygen species acting as stress-response signals, MApKs signaling cascade inducing expression of defense genes, heat shock proteins preventing protein denaturation and degradation, and amino acids pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…In response to withholding water, plants accumulate not only carbohydrate metabolites, but also amino acids (Krasensky & Jonak, 2012). The patterns of several osmoprotective amino acids shown previously to be involved in tomato stress response to abiotic stresses (Gorovits et al, 2020) were notable in plants subjected to drought. Indeed, drought strongly induced several selected amino acids (Figure 4 and Figure S1).…”
Section: Discussionmentioning
confidence: 86%
“…In response to withholding water, plants accumulate not only carbohydrate metabolites, but also amino acids (Krasensky & Jonak, 2012). The patterns of several osmoprotective amino acids shown previously to be involved in tomato stress response to abiotic stresses (Gorovits et al, 2020) were notable in plants subjected to drought. Indeed, drought strongly induced several selected amino acids (Figure 4 and Figure S1).…”
Section: Discussionmentioning
confidence: 86%
“…The HSP 70 protein content in these samples was 51.86 and 48.71 ng × mL −1 , respectively (131 and 123% increase, compared with the control). Gorovits et al [69] also showed an increase in HSP 70 content in tomato leaves treated with pharmaceuticals, in the concentration range of 10-100 µg × L −1 . Even the lowest concentration of pharmaceuticals (10 µg × L −1 ) induced HSP 70 proteins in leaves.…”
Section: Malondialdehyde (Mda) Content Cell Membrane Damage Mitochondrial Activity and Hsp70 Protein Contentmentioning
confidence: 89%
“…Recent studies suggest that pharmaceuticals, similar to low doses of herbicides, may have a negative impact on plant development and agricultural production (Bigott et al, 2021;Carter et al, 2015;Christou et al, 2016;Gorovits et al, 2020Gorovits et al, , 2021. For example, plant exposure to carbamazepine has indicated an effect on plant development, with changes in nutrient and plant hormone concentrations, interference of cell signaling and plant defense and changes in amino acid concentrations and additional osmo-protectants accumulation (Carter et al, 2015;Gorovits et al, 2020Gorovits et al, , 2021. Several studies have also demonstrated that plant exposure to pharmaceuticals may result in changes in the expression of stress related genes (Bigott et al, 2021;Christou et al, 2016).…”
Section: Pharmacodynamics Of Pharmaceuticalsmentioning
confidence: 99%
“…The determination of plant pharmacodynamic biomarkers aims to characterize the exposure or time dependent response of a plant upon exposure to xenobiotic compounds. Biomarker categories include predictive biomarkers which measure any general response/lack of response, or mechanism-of-action biomarkers that allow insights into the pharmacodynamic effects of a drug as well as insight into cellular or sub-cellular responses (Carter et al, 2015;Garralda et al, 2017;Gorovits et al, 2020Gorovits et al, , 2021. Plant pharmacology proposes the establishment of plant pharmacodynamic biomarkers that expand beyond the traditional morphological variations and biochemical changes in plants.…”
Section: Pharmacodynamic Parametersmentioning
confidence: 99%